2008
DOI: 10.1044/1092-4388(2008/001)
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Complexity During Conversation of Boys With Fragile X Syndrome and Down Syndrome

Abstract: Boys with FXS and DS have distinctive language profiles. Although both groups demonstrated syntactic delays, boys with DS showed greater delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
146
4
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(184 citation statements)
references
References 70 publications
15
146
4
19
Order By: Relevance
“…The delay in the development of communicative skills in individuals with DS is foreseen in the literature 7,10,13,19,20,24,25 , even though these individuals do not behave in a homogenous way 10,24 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The delay in the development of communicative skills in individuals with DS is foreseen in the literature 7,10,13,19,20,24,25 , even though these individuals do not behave in a homogenous way 10,24 .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported that to compensate the oral production alterations, lots of children with DS used gestural communication in order to support the words during the application of vocabulary tests [18][19][20]21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations